“Loyalty to organizations” or “loyalty to supervisors”? Research on differential leadership and employee loyalty behavior: A perspective of insiders and outsiders - Zhang, Honglie; Du, Linshen; Jiang, Zhou (Frontiers in Psychology, 2022)
Based on social exchange theory and social learning theory, the relationship between differential leadership and employee loyalty was investigated. The results show that differential leadership has a positive effect on employees' organizational loyalty and supervisory loyalty, and the degree of "loyalty to organizations" is generally lower than "loyalty to supervisors"; under differential leadership style, the supervisory loyalty from insiders is much higher than that from outsiders, but the influence and difference of the two groups(insider and outsider) do not have a significant effect on organizational loyalty. The supervisor developmental feedback mediates the relationship between differential leadership and organizational & supervisory loyalty; power distance positively moderates the relationship between supervisor developmental feedback and organizational & supervisory loyalty, and the higher the perceived power distance of employees, the stronger the indirect effect of developmental feedback from supervisors.